Effects of sintering atmosphere and temperature on physical properties of mullite-based ceramic from black rice husk ash and alumina mixture - Mohamed, Nurzilla (2014)
Mullite (3Al2O3-2SiO2) is well known as a thermal insulator material because of its excellent electrical insulating ability and has been used for various applications. This research was an attempt to study the physical, structural and thermal diffusivity properties of mullite based ceramic prepared by mixing Black Rice Husk Ash (BRHA) and commercial alumina (Al2O3) mixture. Al2O3 powder of purity 99.995% was added to BRHA at 60 % and 80 % percent composition and labeled as samples A (60 wt.% Al2O3-40 wt.% BRHA) and B (80 wt.% Al2O3-20 wt.% BRHA) respectively. The two types of compositions were separately mixed via ball milling for 24 hours. The combinations of BRHA with Al2O3 were pressed into pellets using uniaxial die pressing with an applied pressure of 5 tons to produce the pellets. Samples A and B were sintered in air and nitrogen atmospheres at different temperatures for 2 hours using an electric furnace. The mullite ceramic derived from samples A and B were characterized for physical, structural and thermal diffusivity properties using X-ray diffraction (XRD), X-ray fluorescent (XRF), Fourier transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy (FESEM) micrographs and Laser flash analysis (LFA). The bulk density of samples A sintered in air was increased (2.45 g/cm3 to 2.83 g/cm3) with increasing sintering temperature from 1200 to 1450 oC. However the bulk density of samples A sintered in nitrogen decreased within the range of 2.70 to 2.54 g/cm3 with increasing sintering temperature from 1350 to 1400 oC. Besides that, the bulk density of samples B in both air and nitrogen were increased with increasing sintering temperature. It is noted that the shrinkage percent of sample increased with increase in bulk density of sample. The weight loss of samples sintered in nitrogen is slightly lower compared than samples sintered in air. The bulk density of samples B was found to be higher than samples A which was expected because the quantity of Al2O3 in samples B was higher compared to samples A. The largest linear shrinkage was observed in samples A and this was attributes to the larger amount of BRHA. This variation due to the increase in weight loss for samples A was because of the higher composition of BRHA and hence a larger surface area when compared to samples B. The XRD results revealed that samples A sintered in air at 1450 oC for two hours exhibiting the best results in terms of mullite content. FTIR spectroscopy showed that mullite formation occurred at 1175 cm-1. It was evident from the FESEM micrographs that, samples A sintered in air had a rod-like mullite form with an average grain size increase to 0.25 μm. In contrast, the XRD results of other samples showed a smaller amount of mullite. The results of LFA showed the highest thermal diffusivity at 1450 oC. However, thermal diffusivity sharply decreases with increasing measured temperature from 27 to 500 oC. It was also observed that, the mullite content increased with decreasing Al2O3 addition and increasing of sintering temperature. Thermal diffusivity of samples was diminished due to the presence of impurities in the starting material which contributed to the glassy phase formation.